2019
DOI: 10.1038/s41598-019-49264-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into β-Lactamase-Catalysed Carbapenem Degradation Through Product Characterisation

Abstract: β-Lactamases are a major threat to the clinical use of carbapenems, which are often antibiotics of last resort. Despite this, the reaction outcomes and mechanisms by which β-lactamases degrade carbapenems are still not fully understood. The carbapenem bicyclic core consists of a β-lactam ring fused to a pyrroline ring. Following β-lactamase-mediated opening of the β-lactam, the pyrroline may interconvert between an enamine (2-pyrroline) form and two epimeric imine (1-pyrroline) forms; previous crystallographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 26 publications
14
62
0
1
Order By: Relevance
“…We monitored product formation using the signal corresponding to the C-9 methyl group, which manifests distinctive resonances for the carbapenem starting material, the hydrolysis products, and the β-lactone products (1.22, 1.18, and 1.55 ppm, respectively) (14,15). It should be noted that, in principle, the hydrolysis and lactone products can be produced in two epimeric 1-pyrroline forms [i.e., (S)-Δ 1 imine and (R)-Δ 1 imine], as well as the tautomeric 2-pyrroline (Δ 2 enamine) form ( Figure S5A).…”
Section: Nmr Turnover Assaysmentioning
confidence: 99%
See 3 more Smart Citations
“…We monitored product formation using the signal corresponding to the C-9 methyl group, which manifests distinctive resonances for the carbapenem starting material, the hydrolysis products, and the β-lactone products (1.22, 1.18, and 1.55 ppm, respectively) (14,15). It should be noted that, in principle, the hydrolysis and lactone products can be produced in two epimeric 1-pyrroline forms [i.e., (S)-Δ 1 imine and (R)-Δ 1 imine], as well as the tautomeric 2-pyrroline (Δ 2 enamine) form ( Figure S5A).…”
Section: Nmr Turnover Assaysmentioning
confidence: 99%
“…It should be noted that, in principle, the hydrolysis and lactone products can be produced in two epimeric 1-pyrroline forms [i.e., (S)-Δ 1 imine and (R)-Δ 1 imine], as well as the tautomeric 2-pyrroline (Δ 2 enamine) form ( Figure S5A). Recent work has indicated that the Δ 2 enamine is likely the predominant nascent enzymatic product with most class D SBLs, including OXA-48 and OXA-23 (15). In the case of the products derived from 1βmethyl substituted carbapenems, rapid tautomerization yields the (R)-Δ 1 imine product as the kinetic imine product (which is likely, at least predominantly, a non-enzymatic product) with subsequent conversion to the more thermodynamically stable (S)-Δ 1 imine product ( Figure S5B) (15).…”
Section: Nmr Turnover Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…According to sequence similarity, the beta-lactamases can be classified into four major classes distinguished by the serine residue at the active site, and comprises class A, C and D, whereas class B are metallo-proteinases, which require zinc for their activity [10, 11]. The class A and D active sites of an enzyme resemble each other, showing similarity in their conserved residues [12].…”
Section: Introductionmentioning
confidence: 99%